Assessment of Student Learning at Nusantara Private Junior High School Tanah Jawa Using the Fuzzy Tsukamoto Method - Purba, Jodika Putra Markus; Nailah Hafsah; Harahap, Nesa Pratiwi; Nurhalizah, Shanda; Andani, Sundari Retno (PT Siantar Codes Academy Publisher, 2025)
Student learning assessment is an essential part of the educational process, aimed at determining the achievement of student competencies. However, in practice, assessments often involve elements of subjectivity, particularly in evaluating attitude and participation. Therefore, an approach capable of handling uncertainty and imprecise data is needed. This study aims to develop a student learning assessment system using the Fuzzy Tsukamoto method at Nusantara Private Junior High School Tanah Jawa. The system uses three input variables: assignment scores, exam scores, and student participation. The output of the system is categorized into four assessment levels: Poor, Fair, Good, and Excellent. The results of this study indicate that the Fuzzy Tsukamoto approach can produce outcomes consistent with teacher evaluations and help improve the objectivity of student assessments.